Flexible Design and the Role of the User in House Design - Javier Sanchez (Oz, 2013)
Collective housing became relevant to architecture at the moment of the transformation of production, the moment that Walter Benjamin has characterized as one of technical reproductibility, which formed part of the urban revolution that created metropolization.